Assessing the Effectiveness and Efficiency of Local Government Budget Implementation in Indonesia: A Systematic Review of Value for Money Performance (2016–2023) - Ahmad Haetami; Budi Firmansyah; Abdul Munief Itsniawan; Bayu Rahimansyah Irianto (Journal of Economics and Social Sciences (JESS), 2026)
This study examines the effectiveness and efficiency of local government budget implementation in Indonesia through a Systematic Literature Review of 26 empirical studies published between 2016 and 2023. Guided by the PRISMA framework, the review analyzes Value for Money (VfM) performance and the use of management accounting information in local governments. Findings indicate that while Local Own-Source Revenue (PAD) effectiveness is generally high—often exceeding 100% in several regions—expenditure efficiency remains inconsistent, characterized by under-spending, overspending, and significant regional disparities. Moreover, management accounting information is predominantly used for compliance and reporting purposes rather than for strategic decision-making. Institutional constraints, fiscal dependency, and limited analytical capacity hinder the substantive use of performance information. The study identifies a systematic gap between formal system adoption and meaningful utilization, highlighting the need for stronger integration between accounting practices, governance processes, and public value outcomes.